Konfirmasi Teologis Peran Roh Kudus Dalam Pelayanan Gerejawi - Marciano Antaricksawan Waani; Ester Riyanti Supriadi (CHARISTHEO: Jurnal Teologi dan Pendidikan Agama Kristen, 2021)
The importance of understanding the role of the Holy Spirit becomes a basic need to examine the understanding of the role of the Holy Spirit, especially in ecclesiastical ministry. This paper specifically wants to confirm that the role of the Holy Spirit in ecclesiastical ministry is real. By using a topical method with a qualitative approach to the texts, a theological confirmation as follows regarding the role of the Holy Spirit in ecclesiastical ministry: first, the Holy Spirit teaches. Second, the Holy Spirit testifies. Third, the Holy Spirit guides. Fourth, the Holy Spirit. Fifth, regenerate the Holy Spirit.Keywords: Holy Spirit, church, teaching, witness, guiding, encouraging, being born again. AbstrakPentingnya memahami peran Roh Kudus menjadi kebutuhan dasar untuk meneliti pemahaman tentang peran Roh Kudus khususnya dalam pelayanan gerejawi. Tulisan ini secara khusus hendak memberikan sebuah konfirmasi bahwa peran Roh Kudus dalam pelayanan gerejawi adalah nyata. Dengan menggunakan metode topikal dengan pendekatan kualitatif pada teks-teks Alkitab, maka didapatkan sebuah konfirmasi teologis seperti berikut mengenai peran Roh Kudus dalam pelayanan gerejawi: Pertama, Roh Kudus mengajar. Kedua, Roh Kudus bersaksi. Ketiga, Roh Kudus membimbing. Keempat, Roh Kudus meyakinkan. Kelima, Roh Kudus melahirbarukan.Kata kunci: Roh Kudus, gereja, mengajar, saksi, membimbing, meyakinkan, lahir baru.